2014
DOI: 10.9755/ejfa.v26i7.18187
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and nutritional characterization of Chenopodium pallidicaule (cañ ihua) and Chenopodium quinoa (quinoa) seeds

Abstract: Quinoa (Chenopodium quinoa Willd.) and cañ ihua (Chenopodium pallidicaule Allen) are native Andean food plants of high nutritional value used as food by the Incas and previous cultures. An extensive analytical study was done on three samples for each species for all amino acids, sterols, fatty acids and mineral determination. The aim was to evaluate the chemical and nutritional characterization of cañ ihua and quinoa in relationship with wheat, corn, rice, rye, as sources of dietary fiber and other bioactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
5
20
1
1
Order By: Relevance
“…The calcium content, which is located in the pericarp and seed coat, may be more or less affected by the abrasion process for elimination of saponins, which are found mainly in the outer layer of the seed (Konishi, Hirano, Tsuboi, & Wada, ; Ruales & Nair, ). Lower content of minerals has previously been reported for canihua (Fe 2.5 mg/100 g DM, Zn 2.8 mg/100 g DM, Ca 66 mg/100 g DM), and for amaranth seeds from Peru (Fe 5.0 mg/100 g DM, Zn 1.2 mg/100 g DM, Ca 28 mg/100 g DM) (Repo‐Carrasco‐Valencia et al, ; Villa, Russo, Kerbab, Landi, & Rastrelli, ). The phytate content in pseudocereals is moderate to high in this study and in agreement with the values previously reported for quinoa (752–2,470 mg/100 g DM), canihua (800 mg/100 g DM), and amaranth (1,393 mg/100 g DM) (Lazarte, Carlsson, et al, ; Repo‐Carrasco‐Valencia, Acevedo de La Cruz, Icochea Alvarez, & Kallio, ; Sanz‐Penella, Wronkowska, Soral‐Smietana, & Haros, ; Valencia, Svanberg, Sandberg, & Ruales, ).…”
Section: Discussionmentioning
confidence: 73%
“…The calcium content, which is located in the pericarp and seed coat, may be more or less affected by the abrasion process for elimination of saponins, which are found mainly in the outer layer of the seed (Konishi, Hirano, Tsuboi, & Wada, ; Ruales & Nair, ). Lower content of minerals has previously been reported for canihua (Fe 2.5 mg/100 g DM, Zn 2.8 mg/100 g DM, Ca 66 mg/100 g DM), and for amaranth seeds from Peru (Fe 5.0 mg/100 g DM, Zn 1.2 mg/100 g DM, Ca 28 mg/100 g DM) (Repo‐Carrasco‐Valencia et al, ; Villa, Russo, Kerbab, Landi, & Rastrelli, ). The phytate content in pseudocereals is moderate to high in this study and in agreement with the values previously reported for quinoa (752–2,470 mg/100 g DM), canihua (800 mg/100 g DM), and amaranth (1,393 mg/100 g DM) (Lazarte, Carlsson, et al, ; Repo‐Carrasco‐Valencia, Acevedo de La Cruz, Icochea Alvarez, & Kallio, ; Sanz‐Penella, Wronkowska, Soral‐Smietana, & Haros, ; Valencia, Svanberg, Sandberg, & Ruales, ).…”
Section: Discussionmentioning
confidence: 73%
“…Quinoa seed contains 6.27 to 692.49 mg/kg total saponins, whereas saponin content in amaranth seed is significantly lower at 0.9 to 4.91 mg/kg . At least 16 and 6 saponins have been identified in quinoa and amaranth seed, respectively, which can be divided into three different subgroups containing either oleanolic acid, hederagenin or phytolaccagenic acid as the aglycone .…”
Section: Main Bioactive Components In Quinoa and Amaranth Seedsmentioning
confidence: 99%
“…Current research has suggested quinoa's composition to be as follows: 55.3 % carbohydrates, 12.4 % lipids, and 11.7 % proteins. Quinoa has high-quality proteins (consisting of sulfur, lysine, and aromatic amino acids) and has higher concentrations of amino acids than those the FAO and WHO suggest for grains (Gallego Villa et al 2014). Findings of a 2011 study supported the use of quinoa as a potential source of dietary fiber, polyphenols, and other antioxidants and concluded that extrusion of quinoa (a process allowing foods, such as pastas, to be mass-produced) improves its nutritional value (Repo-Carrasco-Valencia and Serna 2011).…”
Section: A Global Source Of Nutritionmentioning
confidence: 98%